Faktor Yang Mempengaruhi Perilaku Pencegahan Luka Kaki Diabetik Pada Pasien Diabetes - Siti Rohmah (Universitas Galuh, 2019)
Diabetes Mellitus Patients with diabetic foot complications have a significant impact on quality of life, such as loss of mobility associated with sores on the feet that can affect the patient's ability to perform simple everyday tasks. The purpose of this study was to know the effect, directly or indirectly, and the magnitude of the effect of the support of health professionals, knowledge, motivation and attitudes of patients toward prevention behavior foot wounds in diabetic patients in the inpatient unit disease in hospitals Ungaran Semarang. The method used in the study this is a quantitative approach that uses cross-sectional design (cross-sectional). The samples used were 70 patients with diabetes as respondents. The analytical method used is Structural Equation Model (SEM) using SmartPLS 2.0 and SPSS 20. Results of testing the hypothesis by Structural Equation Model (SEM) method smartPLS produce research findings that behavioral variables Prevention LKD in hospitals Ungaran Semarang influenced by the support of health workers (22.86% ), knowledge (20:53%), motivation (22.99%) and attitude (13:34%). The direct effect LKD Behavior Prevention of 79.7% and the indirect influence of 1:19%. Model analysis results can explain the diversity of data and 98.9% were able to examine the phenomenon used in the study, while 1.1% described other components that do not exist in this study. Suggestions studies for hospitals should further improve the provision of in-depth information to patients and families about diabetes prevention as one of the therapeutic efficacy of diabetes mellitus for example by giving leaflets about diabetes mellitus and its complications.Keywords:Health Workers Support, Knowledge, Motivation, Attitude Behavior